Technical Nuances of Autologous Pericranium Harvesting for Dural Closure in Chiari Malformation Surgery - Perrini, Paolo (Journal of Neurological Surgery Part B: Skull Base, 2015)
Duraplasty is a step commonly used for the treatment of Chiari I malformation after foramen magnum decompression. A variety of dural substitutes are currently available for dural closure to minimize the complications related to cerebrospinal fluid (CSF). We describe a technique of harvesting occipital pericranium for duraplasty associated with preservation of a wide cuff of muscle at the superior nuchal line that allows anatomical muscle closure at the end of the procedure. Five symptomatic patients with Chiari I malformation and one patient with syringomyelia-Chiari I complex were operated on with this technique. The indications to perform a duraplasty were accidental arachnoid breaching in three patients during an extra-arachnoidal approach and arachnoidal dissection due to intraoperative findings of arachnoid pathology in the remaining three patients. The overall morbidity of this technique was nil. In all patients the postoperative magnetic resonance imaging scan demonstrated significant expansion of the cisterna magna with no evidence of pseudomeningocele. Duraplasty with autologous pericranium and standardized closure of soft tissues seem promising in reducing the CSF-related complications during Chiari surgery.
Keywords: Chiari I malformation; dural closure; duraplasty; morbidity; pericranial graft